Calidad de servicio y su incidencia en la satisfacción del cliente en las compañías de transporte de carga pesada del cantón La Maná, provincia de Cotopaxi, año 2018. - Medina Briones, Karina Abigail (2019)
Currently, the increasing competition faced by heavy cargo transportation companies has highlighted the challenge of improving their efficiency in the field of quality of service, which is why the present research was carried out, which aimed to analyze the incidence of quality of service in the level of customer satisfaction in the heavy cargo transportation companies in La Maná, which emerged as an alternative solution to the problem of the lack of a model or instruments to improve the quality parameters in an organized manner that allow knowing the level of satisfaction of their users. The proposal was framed within the formative research because it was sought to disseminate existing information and put into practice the knowledge acquired in the classrooms, bibliographic research was used to carry out a bibliographic review on the subject matter of research, field research for collect and record in an orderly manner the data related to quality of care, level of satisfaction and descriptive research to describe the results obtained; We also used the deductive, synthetic analytical methods and the survey technique aimed at partners and users. The results of the diagnosis reflected a low technical level of the drivers in terms of transportation service, absence of a manual of functions and controls on the quality of the vehicles and the level of satisfaction of the users was poor due to the inadequate image of the drivers, the factor of cleanliness and cleaning of the trucks, low level of protection of the load. The calculation of the chi-square showed that the quality of service is dependent on customer satisfaction, which is why strategies were designed based on the quality model European Index of Customer Satisfaction (ECSI) which included the formulation of the vision, mission, values, the expectations strategy with the description of service processes through flowcharts, the driver's function manual, evaluation questionnaire and user loyalty.